Predicting teacher retention behavior: Ex ante prediction and ex post realization of a voluntary retirement incentive offer. (April 2023) - Knapp, David; Hosek, James; Mattock, Michael G.; Asch, Beth J.
Abstract: Teacher retention and retirement decisions are increasingly affected by retirement benefits as the date of retirement eligibility approaches. As part of an effort to rein in operating costs, Chicago Public Schools sought to induce earlier retirement of senior, hence costlier, teachers by offering a voluntary retirement incentive that would be implemented only if enough teachers indicated their willingness to accept it. We used a structural model to predict teacher willingness to take the incentive, and later, when the number of teachers signing up was realized, we compared predictions to the outcomes. We found that the predicted number of willing takers would be less than required to implement the incentive, and this proved true. Further, the predictions were similar to the patterns of takers by age and year of service, though some differences were apparent. We discuss implications for using structural modeling to inform policy design.